The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/10669817.2018.1454087
|View full text |Cite
|
Sign up to set email alerts
|

Pain pattern classification and directional preference for patients with neck pain

Abstract: Pain Pattern Classification (PPC) and Directional Preference (DP) have been shown to be predictive of health care outcomes and serve to guide orthopedic clinical decision making. We conducted a prospective, observational cohort study to verify the association between PPC, DP, and clinical outcomes. Clinical outcome measures including pain intensity and disability were completed at first examination and follow-up by 335 patients. A Pearson's chi-squared test was used to determine differences in prevalence rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…The percentage of change of improvement of disability in our study has reached 30,7%, that outcomes are lower than previous studies where they reached between 50% to 77,77% from immediately to 3 months after (57)(58)(59), but in a recent study no differences for disability was found for McKenzie exercise (60). Two previous observational studies without a control group have shown that the McKenzie method allows for the classification of patients with neck pain and provides improvements in patients in terms of neck disability (61,62). In a recent published systematic review with meta-analysis, they concluded that McKenzie provides very small but statistically significant improvements in neck pain of all severity compared to control interventions (63).…”
Section: Discussioncontrasting
confidence: 72%
“…The percentage of change of improvement of disability in our study has reached 30,7%, that outcomes are lower than previous studies where they reached between 50% to 77,77% from immediately to 3 months after (57)(58)(59), but in a recent study no differences for disability was found for McKenzie exercise (60). Two previous observational studies without a control group have shown that the McKenzie method allows for the classification of patients with neck pain and provides improvements in patients in terms of neck disability (61,62). In a recent published systematic review with meta-analysis, they concluded that McKenzie provides very small but statistically significant improvements in neck pain of all severity compared to control interventions (63).…”
Section: Discussioncontrasting
confidence: 72%
“…Therefore, this study decided on a final sample size with 18 participants who had the derangement syndrome with a DP of cervical retraction or extension. In the general population, the percentage of patients with the derangement syndrome has been reported to be 82% [ 18 ]. Acute and/or traumatic neck pain was excluded in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a secondary analysis of data from a prospective, observational cohort study which examined the association between Pain Pattern Classification (PPC), DP, and clinical outcomes [20]. The current study analyzed data collected from consecutive patients with non-specific neck pain who presented to outpatient clinics and exhibited DP at the first examination in the absence of CEN (see Figure 1).…”
Section: Designmentioning
confidence: 99%
“…Patients were included in this analysis if they presented with complaints of non-specific neck pain with or without radiation into the upper extremities and their cervical spine challenge was classified as DP Non-CEN or DP NC (Non-Classifiable) at first examination; the PPC and DP framework have been described elsewhere [20]. Patients were excluded from the study if they had cervical spine surgery within the preceding 12 months.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation